Asuhan Kebidanan Ibu Hamil Anemia Dengan Pemberian Pisang Ambon Dan Kacang Merah - Ageng Septa Rini; Dwi Rahmawati; Maryam Syarah Mardiyah (JURNAL KESEHATAN MERCUSUAR, 2023)
According to WHO prevalence rate of anemia in the world in 2019 was 41.8%. In 2019, the incidence of anemia in Indonesia was 48.9%. 84.6% of anemia in pregnant women occurs age of 15-24 years. The aim of this care is to determine increase in hemoglobin levels in pregnant women by giving Ambon Bananas and Red Beans at Dr.AK Gani Hospital Palembang 2023. Method in this care is that two pregnant women are divided into 2. Pregnant mother 1 is given Ambon bananas and the pregnant woman 2 was given boiled red beans for 14days, respondent 1 consumed 100 grams Ambon bananas/day and respondent 2 consumed 50grams boiled red beans every morning and evening with 3 hemoglobin level checks, first day, 7day and 14day. With SOAP management. Results show that Ambon bananas increase hemoglobin levels 1.7gr/dL and red beans increase hemoglobin levels 2.2gr/dL pregnant women with anemia. It can be concluded that there is a comparison of hemoglobin levels from giving these 2 interventions, 0.5gr/dL where red beans increase hemoglobin levels more quickly because their iron content is higher than Ambon bananas. Recommended can be applied as an alternative way to treat anemia in pregnant women apart from giving Fe tablets.